Intra-operative arrhythmia predicts post-operative arrhythmia and the need for temporary pacing wires. (4th February 2014) - Piggott, Kurt; Nehgme, Rodrigo; Decampli, William; Pourmoghadam, Kamal; Fakioglu, Harun; Blanco, Carlos
Abstract: Objective: Protocols for the placement of temporary pacing wires vary among institutions. Our current protocol is to selectively place temporary pacing wires in those patients who develop haemodynamically significant intra-operative arrhythmia. We wished to identify how effective our current protocol is at identifying who will develop post-operative arrhythmia and need temporary pacing wires. Methods: The charts of 880 patients over 8 years who underwent cardiopulmonary bypass were reviewed to find patients who developed intra-operative arrhythmia, had temporary pacing wires placed, and whether or not they developed post-operative arrhythmia and required utilisation of the pacing wires. Results: A total of 87 (9.9%) out of 880 patients who required cardiopulmonary bypass over 8 years had intra-operative arrhythmia and had temporary pacing wires placed. Of these, 59 (67.8%) had post-operative arrhythmia and utilised the pacing wires, whereas 28 (32.2%) did not have post-operative arrhythmia or utilise the pacing wires. In all, seven patients who did not have intra-operative arrhythmia or temporary pacing wires placed developed post-operative arrhythmia. Conclusion: Intra-operative arrhythmia is predictive of post-operative arrhythmia (70.2%) and our protocol is a sensitive means of identifying those who will develop post-operative arrhythmia (89.3%).